Penerapan Penerapan Metode Mind Mapping Untuk Meningkatkan Pemahaman Materi Unsur Intrinsik Cerita Mata Pelajaran Bahasa Indonesia - ainun, siti; Masripah, Masripah (Jurnal Cahaya Edukasi, 2025)
Abstract— Students experience difficulties in understanding various materials studied in Indonesian language subjects. one of them, the intrinsik elements of the story. There are several supporting factors so that students gain maximum understanding in the learning process. One of them is, the learning method used. This research was conducted to find out how students understand before and after being given treatment in the form of a mind mapping method on intrinsik story elements. This research uses quantitative research methods with a one group pretest posttest design to compare data on pretest & posttest scores carried out by class V students with a total of 28 students. Learning on intrinsik story element material using the mind mapping method was effective but less efficient because there were some students who were not yet fluent in writing and reading. Students got an average score of 37.35 before being given treatment. The students' pretest posttest results were analyzed using the gain test, getting an NGain value of 0.56, and an NGain percent value of 56.19%. So, students' understanding of the intrinsik elements of stories increased after being treated with the mind mapping method.